How has Cagliari Changed Its Citizens in Smart Citizens? Exploring the Influence of ITS Technology on Urban Social Interactions - Coni, Mauro; Garau, Chiara; Pinna, Francesco (Computational Science and Its Applications - ICCSA 2018, 2018)
The main purpose of this article is to evaluate and to achieve a deeper understanding of the changing role of Intelligent Transport Systems (ITSs) not only in transport habits, but also in urban traditional lifestyles of citizens, by using the city of Cagliari (Italy) as a case study. In fact, ITSs play a significant role in determining innovative sustainable transport, for a better use of urban space and time, enhancing also the people quality of life. ITSs help people to move around more easily, safely and economically, in a more environmentally friendly manner. Traditionally, ITSs were used to improve traffic flow, cars speed, easy parking and therefore encouraging the use of the cars, by causing negative impact on social interactions. Nowadays, cities are changing and use technology in order to greatly improve public transport and smart mobility. Specifically, this study analyzes the city of Cagliari (Italy) and its transition toward a smart, sustainable and green mobility, by showing the successful steps from a scenario based on a car-used city to a new scenario based on a free cars-used city due to an integrated, environmental, smart approach.